The effects of human population density on trophic interactions are contingent upon latitude - Aagaard, Natalia Desiré (2024)
Aim: Global-scale studies are necessary to draw general conclusions on how trophic interactions vary with urbanization and to explore how the effects of urbanization change along latitudinal gradients. We predict that the intensity of trophic interactions decreases in response to urbanization (quantified by human population density). Since trophic interactions are more intense at lower latitudes, we also expect major impacts of urbanization at higher latitudes, where base levels are essentially lower. Location: Global (881 study sites). Time period: 2000–2021. Major taxa studied: Birds, arthropods and woody plants. Methods: We compiled global data on insect herbivory and bird predation from studies that employed similar methods and fitted generalized linear mixed models to test how these trophic interactions vary with human population density, latitude and their interactions. Results: The intensity of herbivory and predation decreased with an increase in human population density at lower latitudes. Surprisingly, it remained unaffected at intermediate latitudes and even increased at higher latitudes. Main conclusions: The observed patterns may be attributed to local climate changes in urban areas, such as the Urban Heat Island effect, which disrupts thermal stability in the tropics while increasing niche availability at polar latitudes.